Quality of Muaro Sasak Waters, West Pasaman Regency, West Sumatra Province: Kualitas Perairan Muaro Sasak, Kabupaten Pasaman Barat, Provinsi Sumatera Barat - Alya, Alya Fariani; Kamal, Eni; Razak, Abdul (Universitas Negeri Padang, 2023)
West Pasaman Regency, especially the coastal area of Sasak Subdistrict is an area that supports sustainable fisheries activities for the Sasak Subdistrict community, so it is important to know the quality of its waters. This study aims to determine the quality of waters in Muaro Sasak based on chemical parameters which are then compared with the quality standards of the research instruments used. The research was conducted at two sampling points namely Batang Pasaman and Batang Kapar. Water quality parameters measured include acidity (pH), temperature, dissolved oxygen (DO meter), total dissolved solids (TDS) measured in-situ. The results of water quality research in Batang Pasaman showed a pH value of 5.5-6.5, temperature of 29-31˚C, DO meter 3.12-5.87 ppm, and TDS meter 620-720 ppm. While the results of measurement analysis in Batang Kapar showed a pH value of 5.2-5.5, temperature 35˚C, DO meter 3.55-4.21 ppm, and TDS meter 710-810 ppm